PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 165 PEKANBARU - Irma Nurliyanti; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The subjects is research students public elementary school III Pekanbaru, in social studies with a number of students 35 people. Which consisted of 19 male students and 16 female students. This type of research is the PTK (action research) is a research done in class in order to improve/enhance the quality of teaching practices. This research was conducted precisely in November 2014 consisted of 11 cycles. KKM predetermined value is 75, but only 42.85% (15 people) who attain KKM. While 57.15% (20 people) who received grades below a predetermined KKM. By applying the learning model Numbered Head Together (NHT). IPS learning outcomes by using cooperative learning model NHT higher than the learning outcomes before using cooperative learning model NHT. The average initial 64.14, after learning using NHT, increased learning outcomes of scores UH, which is an average increase of 64.14 into 76.28 by 18.92% increase learning outcomes IPS from the base score to UH 2 an average of 64.14 into 82.17 with an increase of 28.95%. This proves that the application of the learning model NHT cooperatif can improve learning outcomes IPS third grade students of SDN 165 Pekanbaru.Keywords: Numbered Head Together (NHT), Learning IPS, IPS Learning Outcomes